Patient Satisfaction with Quality of Dentures at Teaching Hospital of Lahore: Quality Dentures and Patients Satisfaction - Qamar, Khezran; Rizvi, Syed Hammad Azeem; Yasser, Faiqua; Aamir, Hira; Ahmed, Rana Ammar; Muzaffar, Maham; Naeem, Sajid (Pakistan Journal of Health Sciences, 2024)
Complete dentures are fabricated to restore functional and esthetic needs of edentulous patients. Poor psychomotor abilities undermine their satisfaction level with well fabricated dentures and prosthodontic treatment becomes unsuccessful. Objective: To evaluate the patient’s satisfaction level with newly inserted complete dentures fabricated by final year students and senior prosthodontists. Methods: The cross-sectional observational study population comprised of completely edentulous patients. The study conducted at Prosthodontic department of Lahore Medical and Dental College Lahore; from 8th June till 8th December 2023.A questionnaire was designed to assess parameters. Likert scale was used to answer; ranging from 1 to 5 where 1 is the poorest and 5 is the best value. Dentist, gender and previous experience were compared with patient satisfaction parameters. Results: Out of 62 complete denture patients; 72.6% had no denture wearing experience. 43.5% tooth loss was due to caries followed by periodontitis. Tooth loss in past 5 years’ time was 61.3%. Denture aesthetics was rated as good 46.8%. Patient satisfaction parameters with age group and doctor group showed significant association. Correlation of patient satisfaction parameters with doctor group was statistically significant for mandibular denture speech, mandibular function and operator service p-value <0.05. Conclusions: Patient satisfaction with removable prosthesis determines the success of the prosthodontics intervention. Evaluation of patients’ satisfaction level should be carried out routinely after the completion of the treatment as will help in the improvement of the work quality of a dental practitioner.